RADI-06. CORRELATION BETWEEN APT-CEST AND 18F-CHOLINE PET IN GLIOMA AT 3T. Issue 2 (22nd June 2018) - Rega, Marilena; Torrealdea, Francisco; Hearle, Joe; Zaiss, Moritz; Cavalho, Ana; Afaq, Asim; Punwani, Shonit; Golay, Xavier; Dickson, John; Shankar, Ananth; Hyare, Harpreet
Abstract: INTRODUCTION: Chemical exchange saturation transfer (CEST) MRI is emerging as a powerful diagnostic tool in gliomas but there is lack of agreement as to the source of the Amide Proton Transfer (APT)-CEST signal and contrast. We aimed to investigate whether APT signal could be a non-invasive biomarker of Teenage and Young Adult (TYA) glioma cell proliferation through correlation with 18 F-Cho PET SUV as the gold standard. METHODS: 8 TYA patients referred for 18 F-Cho PET-MRI with suspected glioma were recruited for APT-CEST acquired with a gradient echo based snapCEST acquisition (12 studies). Regions of interest (ROI) of the 'non-enhancing', 'enhancing' and 'necrotic core' in the tumour and healthy 'white matter' (WM), were segmented from T2w-FLAIR and T1w-postGd images. RESULTS: The strongest correlation was observed for APT-CEST versus 18 F-Cho PET (Spearman ρ = 0.85, p<0.001) and the highest APT-CEST signal was seen in the enhancing and necrotic core ROIs. APT-CEST distinguished the non-enhancing tumour ROI from normal white matter (p<0.001) whilst 18 F-Cho PET SUV could not (p>0.05). DISCUSSION: This feasibility study presents the first comparison of APT-CEST and 18 F-Cho PET in patients with TYA gliomas. The strong positive correlation indirectly demonstrates that APT-CEST may be a marker of glioma cell proliferation and further demonstrates the potential of APT-CEST in the assessment of glioma burden. Importantly, APT-CEST could be a useful adjunct in monitoring disease activity in 18 F-Cho negative non-enhancing tumour.